The cartilaginous tissue formation using sry (Sex determining region Y)-BOX9 and telomerase reverse transcriptase genes transfected chondrocytes: In vivo approach = Formasi tisu tulang rawan menggunakan sry (Penentu jantina rantau Y)-BOX9 dan telomeras gen transkripsi berbalik kondrosit transfeksi: Pendekatan in vivo) - Md Nazir, Noorhidayah; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Zainol, Ismail; Zamli, Zaitunnatakhin; Sha'ban, Munirah (Penerbit UKM, 2020)
The shortage of organ supply reduces the success rate of organ transplantation. Hence, tissue regeneration has been initiated with the intention of improving the available treatment modalities. Articular cartilage is a suitable tissue for this purpose due to its limited self-heal ability. This study aims to evaluate the cartilaginous properties of in vivo constructs formed using chondrocytes transfected with the combination of sry (sex determining region y)-box9 (SOX9) and telomerase reverse transcriptase (TERT) genes (SOX9/TERT-transfected chondrocytes) seeded on a three-dimensional (3D) poly(lactic-co-glycolic) acid (PLGA)-based scaffold. The rabbit’s articular chondrocytes (n=6) were transfected with SOX9 and TERT genes via lipofection. The non-transfected chondrocyte (NTC) was used as a control. A total of 1×105 cells were seeded on a PLGA and PLGA/fibrin hybrid scaffolds to form constructs. The resulted constructs were SOX9/TERT-PLGA/fibrin, NTC-PLGA/fibrin, SOX9/TERT-PLGA and, NTC-PLGA. All constructs were cultured for three weeks prior to subcutaneous implantation into the athymic mice for two and four weeks. The constructs’ structural and functional aspects were evaluated using macroscopic observation, compression-stress analysis, histology, quantitative sulphated glycosaminoglycan (sGAG) assay and cartilage-specific genes (ACAN, COL2A1, SOX9), TERT, and MMP13 expression analysis. The constructs demonstrated a cartilage-like appearance. The constructs’ rigidity corresponded to the homogenous cells and extracellular matrix distribution in the week-4 constructs. Correspondingly, the cartilaginous matrix components were visualised at the pericellular matrix region of the construct, supported by the increment of quantitative sGAG content. The SOX9/TERT-PLGA/fibrin exhibited better genes expression and cartilaginous phenotypes than the other construct groups. The SOX9/TERT-PLGA/fibrin construct facilitated cartilaginous tissue formation.